Experimental and Simulation Study of n-Heptane Adsorption on Rutile - Prates Ramalho, João Paulo (2008)
The adsorption of n-heptane on microcrystalline rutile has been studied experimentally by thermodynamic techniques (adsorption isotherms and microcalorimetry) over a wide range of coverage at 303 K and complemented by Grand Canonical Monte Carlo simulations. The differential heat of adsorption exhibited three descending segments corresponding to the adsorption of n-heptane on three types of surfaces. The mean molar adsorption entropy of n-heptane in the monolayer was less than the entropy of the bulk liquid by ca. –23 J/(mol K), thus revealing a hindered state of motion for the n-heptane molecules on the surface of rutile. Simulations of the adsorption of n-heptane were performed on the three most abundant crystallographic faces of rutile. The adsorption isotherm obtained from the combination of the isotherm for each face weighted by the respective abundance was found to be in good agreement with experimental data. A structural characterization of n-heptane near the surface was also conducted which indicated that the substrate strongly perturbed the distribution of the n-heptane conformations relative to the situation found for the gaseous phase. Adsorbed molecules are predominantly orientated with their long axes, with the zig-zag planes of their backbones parallel to the surface and preferentially aligned along the five-fold cus Ti4+ ions of the faces. Fewer gauche conformations were observed for molecules near the surface than was characteristic of the bulk phase.